Expression of Neo-Vernacular Architectural Concept in Recreational Commercial Building (Study Case: Tip, Hotel And Resort, Actic) - Adi Heriyanto; Gagoek Hardiman; R. Siti Rukayah (Eduvest - Journal of Universal Studies, 2025)
Neo-vernacular architecture is a postmodern architectural style that is a combination of two different concepts, namely modern and vernacular architecture to express a more contemporary vernacular architecture. Recreational commercial buildings are buildings used for business or recreational commercial activities that are usually uniquely designed to be attractive and comfortable for visitors who apply the expression of neo-vernacular architectural concepts in their design. This research aims to find out the character of neo-vernacular architecture in recreational commercial buildings and how it is applied so that it can be used as a reference for the community or the government in designing recreational commercial buildings with this concept. This study uses a qualitative descriptive method that is expected to describe the character of neo-vernacular architecture and its application to buildings. The research locations include the Semarang-Surabaya toll road, namely Pendopo kilometers four, five, six, Salatiga, ono joglo and Jepara resorts, as well as the Asasuka Japan Tourist Information Center. The analysis in this study uses neo-vernacular architectural theory. The results of this study conclude that the expression of the neo-vernacular architectural concept in the three case studies of recreational commercial buildings appears to be very strong in the design of the roof shape that adopts local icons (vernacular) of ridge roof types such as joglo, limasan, saddle, baked pe.